PENGARUH JUMLAH PENDUDUK, INVESTASI DAN KONSUMSI RUMAH TANGGA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI PROVINSI SUMATERA UTARA - Wida Raskina; Saharuddin Saharuddin (LPPM UNIMAL, 2022)
This study examined the effect of population, investment, and household consumption on the Gross Regional Domestic Product (GRDP) in North Sumatra Province. The data analysis method used was quantitative data in the form of secondary data with a multiple linear regression model with E-views 10, where the total number of observations was 16, with the number of years consisting of 2004-2020. The results revealed that the population influenced GDRP in North Sumatra Province, Investment did not influence GRDP in North Sumatra Province, and Household consumption did not influence GRDP in North Sumatra Province.